Efeitos do pré-aquecimento de blendas de óleo de fritura e biodiesel com óleo diesel utilizadas como combustível em queimadores - Tondo, Wellington Lucas (2015)
The large consumption of fossil fuels that still today predominates the world's energy supply is one of the great villains in greenhouse gases emissions (GHG), that are largely responsible for global warming. The oil reserves tend to depletion, and the growing demand of energy needed to feed the technological advances, the search for solutions to minimize emissions of pollutants and waste recovery, discarded improperly by man, became an opportunity to add value and produce energy from raw materials, that cause major environmental impacts. The biodiesel from waste frying oil has been shown to be effective alternative in renewable energy production, as well as having large potential energy, generates by-products that may be incorporated in the processing of raw materials, adding final value. This work evaluated the use of blends of diesel oil with oil and biodiesel from waste frying, in fixed and varying proportions of 10% for each treatment, B0 being the absence of biodiesel and B100 being entirely, as an alternative renewable fuel in burners for heating of pools. The conduct of the experiment occurred in the thermal pool block physiotherapy State University of Western Paraná (UNIOESTE), during the month of August 2014, in the Cascavel campus, using entirely randomized design. The fuels were evaluated for their behavior at room temperature and passing through a heating process, which on average was 50,63 °C, before to combustion in the burner. We evaluated data: percentage of water and impurities, viscosity, density, calorific value, emission of CO2, O2, and the exhaust temperature in the produced blends. Were also collected input and output temperature information in the boiler, flow water, flow and fuel temperature, to determine the specific consumption and efficiency. There was a reduction in thermal efficiency of the system, as increased the percentage of biodiesel contained in mixtures, operating at room temperature. However, with the pre-heating, we obtained a significant improvement. KEYWORDS: